Development of two instruments for assessing maternity health needs: protocol of a clinimetric study - Paz-Pascual, Carmen; Artieta-Pinedo, Isabel; Espinosa, Maite; Bully, Paola (BMC pregnancy and childbirth, 2020)
Background There is an unquestionable need to adapt health care to the needs of each woman, to foster her self-confidence and provide her with the autonomy to manage her own maternity. This involves empowering her to choose and face her model of childbirth and childcare responsibly. The range of self-management health needs tests offered by the scientific community at this stage of life is practically non-existent. In this project, we intend to develop and evaluate the validity, reliability and ease of use of two self-administered analysis instruments for: 1.- Needs of women preparing for childbirth and 2.- Identification of alarm symptoms in the puerperium. Methods This is a descriptive study of the clinimetric characteristics and usability of two developed self-applied digital instruments for measuring needs in childbirth and postpartum based on the recommendations made in the consensus-based standards for the selection of health measurement instruments (COSMIN) and by the International Test Commission (ITC). The study consists of two phases: 1 - Evaluation of the clinimetric properties of the two instruments, which were developed and then altered, based on their comprehensibility and global usability estimated from a pilot study and 2 - Pre-implementation study. Discussion The final product will be two valid, reliable, usable instruments for self-assessment of health needs that are highly acceptable to young couples and the professionals who serve them. They will be a valuable resource for meeting the needs of the population more efficiently and guiding decision-making, and they will contribute to the greater sustainability of the health system.